Assessment of Patients’ Knowledge, Perception and Safety Regarding MRI Scan - Shrestha, Susmita; Khadka, Bibek (Journal of Manmohan Memorial Institute of Health Sciences, 2020)
Correction: The page numbers on this article were changed from 4-20 to 3-19 on 31/08/2020. Introduction: We presume that the knowledge of patients about Magnetic Resonance imaging (MRI) scan is of utmost importance for smooth workflow, patient comfort, patients’ safety and to mitigate patients’ compliance and save valuable scan time. Therefore, the purpose ofthis study was to determine the awareness of patients undergoing MRI scan regarding Knowledge, Perception and Safety. Methods: This descriptive cross-sectional study was carried out in Chitwan Medical College Teaching Hospital from April to September, 2018. Total of 310 patients referred to undergo MRI scan were assessed by a questionnaire form covering 4 parts: Part 1- aimed to gather the socio demographic data such as age, sex, occupation and educational status of patients, Part 2- included the knowledge regarding MRI and its safety, Part 3- comprised the patient perception before MRI scan and Part 4 constituted the patient perception after MRI scan.The form was filled by an investigator oneself in a face to face interview with the patients. Results: Among 310 patients, 35.2% were illiterate and 19.4% graduated from high school. Majority of 85.5% patients answered that MRI uses harmful ionizing radiation like CT scan and radiography. Almost 43 patients who answered MRI functions in disease treatment also answered decreased in pain after MRI scan (Male = 15 and Female = 28) were in age group between 25 years and 50 years. This study also revealed that majority of 26.8% (i.e. n = 83) patients faced problem as claustrophobia along with anxiety during the scan, out of which 13 patients have history of previous MRI scan. Conclusions: In our study decrease in pain was higher in diagnosis and treatment answer. Majority of the patients faced anxiety along with claustrophobia during the MRI scan. Assessment of patient knowledge, perception and safety regarding MRI scan can be the key to increase patient compliance and save valuable scan time.